2012
DOI: 10.1093/cercor/bhs007
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Executive Components of Working Memory

Abstract: Working memory (WM) enables the online maintenance and manipulation of information and is central to intelligent cognitive functioning. Much research has investigated executive processes of WM in order to understand the operations that make WM "work." However, there is yet little consensus regarding how executive processes of WM are organized. Here, we used quantitative meta-analysis to summarize data from 36 experiments that examined executive processes of WM. Experiments were categorized into 4 component fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
395
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(440 citation statements)
references
References 116 publications
40
395
3
2
Order By: Relevance
“…Recent quantitative meta-analyses have shown that engagement during verbal WM tasks can be seen bilaterally within the DLPFC, PAR and ACC (Wager and Smith, 2003;Nee et al, 2013) although left-sided involvement was more common (Nee et al, 2013). However previous studies (Altamura et al, 2007;Kirschen et al, 2005) as well as the current study suggest that the key driver of lateralisation within the verbal WM network is memory load.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Recent quantitative meta-analyses have shown that engagement during verbal WM tasks can be seen bilaterally within the DLPFC, PAR and ACC (Wager and Smith, 2003;Nee et al, 2013) although left-sided involvement was more common (Nee et al, 2013). However previous studies (Altamura et al, 2007;Kirschen et al, 2005) as well as the current study suggest that the key driver of lateralisation within the verbal WM network is memory load.…”
Section: Discussioncontrasting
confidence: 71%
“…the total demand on maintenance, updating and manipulation processes) (Braver et al, 1997;Callicott et al, 1999;Owen et al, 1999;Volle et al, 2008) and may be sensitive to content being leftlateralised for verbal and right-lateralised for spatial and object information (Fletcher and Henson, 2001;Wager and Smith, 2003;Nee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be the case that each of these abilities are important but for different EF components. For example, working memory has been found in several previous studies to be an important component of EF (Monette et al 2011;Nee et al 2013). Working memory was also found to be important in this study; however, the current study adds to the literature in suggesting the degree of language demands in WM tasks is an important distinguishing quality of EF tasks in preschool children.…”
Section: Discussionsupporting
confidence: 41%
“…There is some meta-analytic evidence for regional specificity, including interactions between manipulation demand and material type (Wager and Smith 2003). However, a more recent metaanalysis of 36 event-related fMRI studies found only limited support for specificity (Nee et al 2013; see further the updating section below). Instead, it found that four manipulation processes ( protect from external distraction, prevent intrusion of irrelevant memories, shifting of attention, and updating the contents of working memory) engaged several overlapping frontal regions.…”
Section: How Can Information In Working Memory Be Manipulated and Updmentioning
confidence: 99%
“…The necessity of a dynamic relation between maintenance and updating has been captured in terms of a "gating mechanism"; a closed gate promotes maintenance, an open gate allows updating. There is evidence from functional imaging that parts of the frontal cortex are more active during working-memory updating relative to other forms of working-memory manipulation, such as inhibition (Dahlin et al 2008) and shifting of attention (Nee et al 2013). However, it has been argued that it is only through interactions with the basal ganglia that the prefrontal cortex realizes this gating function (O'Reilly 2006), such that the striatum provides gating signals to the frontal cortex (Go/update or NoGo/ maintain) via interactions with the thalamus and the substantia nigra.…”
Section: A Subcortical Dopaminergic Updating Systemmentioning
confidence: 99%